2015
DOI: 10.11152/mu.2013.2066.173.rch
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted identification of the gingival sulcus and periodontal epithelial junction on high-frequency ultrasound images

Abstract: The primary aim of this study was to demonstrate that periodontal ultrasonography is a reliable method with which to identify and evaluate the attachment level of the gingival junctional epithelium. A secondary aim was to devise an automated computer-assisted method that allows the examiner to more easily identify the gingival sulcus contour on ultrasound images. Material and methods: This in vitro study was carried out on 36 sites on the lingual surface of eight pig mandibles. For each site, periodontal ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Computer-assisted identification of the gingival sulcus and the periodontal epithelial junction on high-frequency ultrasound images lies in the identification and visualization of the gingival sulcus on US images, without the need of a periodontal probe that could influence the gingival attachment level. Moreover, the computer algorithm used in the analysis significantly increased the accuracy of the measurements, as confirmed by the fact that the values did not significantly differ from those obtained by microscopy 4X magnification as a gold standard of the same section as the ultrasonographic one [10].…”
Section: S25mentioning
confidence: 73%
See 2 more Smart Citations
“…Computer-assisted identification of the gingival sulcus and the periodontal epithelial junction on high-frequency ultrasound images lies in the identification and visualization of the gingival sulcus on US images, without the need of a periodontal probe that could influence the gingival attachment level. Moreover, the computer algorithm used in the analysis significantly increased the accuracy of the measurements, as confirmed by the fact that the values did not significantly differ from those obtained by microscopy 4X magnification as a gold standard of the same section as the ultrasonographic one [10].…”
Section: S25mentioning
confidence: 73%
“…A much smaller probe was developed, a periodontal probe, as a spin-off of NASA technology. An ultrasonic transducer projects high frequency (10)(11)(12)(13)(14)(15) ultrasonic energy between the tooth and the gum and detects echoes of the returning wave. In the usual practice of ultrasonography, the time delay of the reflection is converted to a distance measurement by using the speed of sound in water (1482 m/s).…”
Section: Bidimensional Periodontal Ultrasonographic Investigations Umentioning
confidence: 99%
See 1 more Smart Citation
“…This pilot study showed that OCT is suitable for in vivo humans imaging of the microscopic appearance of gingival sulcus and nearby tissues without any adverse side effects, artifacts or staining procedures. Thus, a clinical methodology was adopted and comparison was made with traditional probes and promising technologies such as ultrasonic probing and computerized probing with optical fiber sensors .…”
Section: Discussionmentioning
confidence: 99%
“…Sanchez [8] proposed a useful tool for identifying patients at high risk of stroke and selecting those who can benefit most from revascularization therapies such as carotid endarterectomy and stenting. Chifor [9] demonstrated that periodontal ultrasonography is a reliable method with which to identify and evaluate the attachment level of the gingival junctional epithelium. Vatansever [10] proposed fetal neuroimaging study that provide normal posterior fossa growth trajectories during the second and third trimesters of pregnancy via semi-automatic segmentation of reconstructed fetal brain MR images and to assess common cerebellar malformations in comparison with the reference data.…”
Section: Introductionmentioning
confidence: 99%